Explicit Instruction Model in Improving Mathematics Learning Outcomes in Matrix Material - Salsabila, Salsabila (EDUCTUM: Journal Research, 2023)
The success of the mathematics learning process can be seen from the learning outcomes achieved by students after carrying out the mathematics learning process. Mathematics learning outcomes are students' abilities obtained after learning activities. One of the problems that is often encountered in mathematics learning is usually when students are unable to work on mathematics problems due to a lack of understanding of students' concepts, thus affecting the students' learning outcomes. Many factors influence students' mathematics learning outcomes, one of which is the learning model. The Explicit Instruction Learning Model is a direct teaching designed to develop students' knowledge to solve problem stages and the ability to remember. So that students can understand the learning step by step about the Absolute Value material.